Discursive Constructions in Televised News: The Case of Mindanao, Philippines - Ladrido, Estelle Marie Macuja (Archīum Ateneo, 2022)
News stories carry boundary setting language that constructs nations as homogenous imagined communities and furthers the us-vs-them metanarrative that separates those who belong to one nation from those who do not. However, it may be possible that boundary-setting representations may be applied to groups within the nation-state. This article explores this possibility by examining the discourse constructed by mediated communication such as local and national television news programs about the Mindanao region in the southern Philippines. Results show that Mindanao-based journalists present Mindanao to local viewers as different, neglected, and violent. This is possibly an indication of how historical social processes involved in the emergence of the Mindanao state intersect the discursive ones concerned with national and regional identity construction.